Optimization of ethanol production using newly isolated ethanologenic yeasts - TOKSOY ÖNER, EBRU (ELSEVIER, 2021)
Yeasts are important microorganisms used for ethanol production; however, they are not equally efficient in the amount of ethanol production under different environmental conditions. It is, therefore, necessary to screen for elite strains to utilize them for commercial production of these commodities. In this study, yeasts were isolated from different Ethiopian traditional fermented alcoholic beverages (teji, tella, shamiata and areqe tinisis), milk and ergo, teff and maize dough, soil and compost, flowers, and fruits to evaluate their potential use for ethanol fermentation process. Isolates were screened for efficient ethanol production and the selected ones were identified using phenotypic and genetic characters using D1/D2 region of LSU rDNA sequence analysis. The yeast isolates were evaluated based on their growth and fermentation of different carbon sources. Response surface methodology (RSM) was applied to optimize temperature, pH and incubation time using central composite design (CCD) in Design-Expert 7.0.0. A total of 211 yeasts colonies were isolated of which 60% were ethanologenic yeasts (ethanol producers) and 40% were non-ethanol producers. The yeast population detected from various sources was in the range of 10(5) CFU from traditional foods and beverages to that of 10(3) CFU from fruits and soil samples. The data also showed that the number of colony types (diversity) did not correlate with population density. The highly fermentative isolates were taxonomically characterized into four genera, of which 65% of the isolates (ETP37, ETP50; ETP53, ETP89, ETP94) were categorized under Saccharomyces cerevisiae, and the remaining were Pichia fermentans ETP22, Kluyveromyces marxianus ETP87, and Candida humilis ETP122. The S. cerevisiae isolates produced ethanol (7.6-9.0 g/L) similar with K. marxianus ETP87 producing 7.97 g/L; comparable to the ethanol produced from commercial baker's yeast (8.43 g/L) from 20 g/L dextrose; whereas C. humilis ETP122 and P. fermentans ETP22 produced 5.37 g/L and 6.43 g/L ethanol, respectively. S. cerevisiae ETP53, K. marxianus ETP87, P. fermentans ETP22 and C. humilis ETP122 tolerated 10% extraneous ethanol but the percentage of ethanol tolerance considerably decreased upon 15%. S. cerevisiae ETP53 produced ethanol optimally at pH 5.0, 60 h, and 34 degrees C. pH 4.8, temperature 36 degrees C, and 65 h of time were optimal growth conditions of ethanol fermentation by K. marxianus ETP87. The ethanol fermentation conditions of P. fermentans ETP22 was similar to S. cerevisiae ETP53 though the ethanol titer of S. cerevisiae ETP53 was higher than P. fermentans ETP22. Therefore, S. cerevisiae ETP53, K. marxianus and P. fermentans ETP22 are good candidates for ethanol production.
Keywords: Candida humilis; Kluyveromyces marxianus; Pichia fermentans; Saccharomyces cerevisiae; Yeast; Ethanol production; SACCHAROMYCES-CEREVISIAE; KLUYVEROMYCES-MARXIANUS; SIMULTANEOUS SACCHARIFICATION; THERMOTOLERANT YEAST; FERMENTATION; FLOCCULATION; TOLERANCE; STARTER; STRAIN; ACID